2018
DOI: 10.1002/ncp.10003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Prevalence of Muscle Weakness (Sarcopenia) in Haemodialysis Patients Determined by Hand Grip Strength Due to Variation in Guideline Definitions of Sarcopenia

Abstract: There is currently no agreed universal definition for sarcopenia, but the EWGSOP and FNIH advocate HGS cut-offs as part of their definition. The prevalence of muscle weakness varies according to cut-off and whether age-matched and gender-matched normative data are used. In addition, patient characteristics in terms of age and comorbidity determine the prevalence of muscle weakness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
(76 reference statements)
1
10
1
Order By: Relevance
“…We read the article by Tangvoraphonkchai et al “Differences in Prevalence of Muscle Weakness (Sarcopenia) in Haemodialysis Patients Determined by Hand Grip Strength Due to Variation in Guideline Definitions of Sarcopenia” with great interest 2 . We have a comment on this well‐designed paper.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…We read the article by Tangvoraphonkchai et al “Differences in Prevalence of Muscle Weakness (Sarcopenia) in Haemodialysis Patients Determined by Hand Grip Strength Due to Variation in Guideline Definitions of Sarcopenia” with great interest 2 . We have a comment on this well‐designed paper.…”
contrasting
confidence: 57%
“…1 We read the article by Tangvoraphonkchai et al "Differences in Prevalence of Muscle Weakness (Sarcopenia) in Haemodialysis Patients Determined by Hand Grip Strength Due to Variation in Guideline Definitions of Sarcopenia" with great interest. 2 We have a comment on this welldesigned paper. The authors noted that muscle weakness was suggested in EWGSOP cutoff definitions as 32 kg for males and 22 kg for females, but these cutoff thresholds were from hand grip strength in the Turkish population from our study-not EWGSOP 1.…”
Section: Reference Cutoff Values For Muscle Strength In Different Natmentioning
confidence: 99%
“…In nephrology, there is a vast number of terms for malnutrition, including uremic malnutrition 61 , kidney cachexia/uremic cachexia 62 , sarcopenia in kidney disease 63,64 , malnutrition, inflammation, and atherosclerosis (MIA) syndrome [65][66][67][68] or malnutritioninflammation complex syndrome (MICS), proteinenergy malnutrition 69 and protein-energy wasting 70,71 . Each definition of malnutrition validated for this group of patients includes different sets of criteria.…”
Section: Level Of Evidence B Strength 1 Commentsmentioning
confidence: 99%
“…Hemodialysed patients (HDPs) frequently suffer from muscle weakness [1], frailty [2], and falls [3,4]. This continuous loss of muscle mass and functions across life-time spent on dialysis therapy causes frequent health problems in HDP.…”
Section: Introductionmentioning
confidence: 99%